Walt Disney's Peter Pan. - Barrie, J. M. (James Matthew), 1860-1937.; Walt Disney Company (Danbury, Conn. : Grolier Enterprises, Inc., 1993)
The adventures of the three Darling children in Never Land with Peter Pan, the boy who would not grow up.
"Disney's wonderful world of reading" -- cover.
"Grolier book club edition".
Keywords: Fantasy; Peter Pan (Fictitious character) -- Fiction